Dual-emission fluorescent carbon dots, visual hydrogel sensing platform prepared from dual-emission fluorescent carbon dots and application of visual hydrogel sensing platform
By developing dual-transmitted fluorescent carbon dots (DE-CDS) and smartphone-assisted hydrogel sensing platforms, the problem of unable to achieve real-time detection of the existing tetracycline detection method can be solved. Essence
Patent Information
- Application Number
- CN202411496842.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
The existing tetracycline detection methods require expensive instruments and professional technicians, and cannot achieve portable on-site real-time detection.
A dual-transmitted fluorescent carbon dot (DE-CDS) and its prepared visual hydrogel sensing platform were developed, and real-time detection of tetracycline was used to help tetracycline with smartphones.
The fast, accurate and portable detection of tetracycline has been achieved. The detection limit is 53.4 nm, and the system response time is 4 minutes, which improves the real -time and portability of the detection.
Smart Images

Figure CN119371964A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of fluorescence detection technology, and specifically relates to a dual-emission fluorescent carbon dot and a visualized hydrogel sensing platform prepared therefrom and its application. The sensing platform is a smartphone-assisted hydrogel sensing platform for portable on-site detection of tetracycline. Background Art
[0002] Tetracycline (TC) is a widely used antibiotic that has been widely used in medicine, animal husbandry and aquaculture due to its effective antibacterial properties, low cost, few side effects and good therapeutic effects [1]. However, excessive use of tetracycline can lead to tetracycline residues in soil, water and food. These residues may enter the human body mainly through the food chain, posing a risk to human health [2]. Traditional tetracycline detection methods, such as high performance liquid chromatography (HPLC) [3], liquid chromatography-mass spectrometry (LC-MS) [4] and enzyme-linked immunosorbent assay [5], are known for their high accuracy and sensitivity. However, these methods have certain limitations, including the need for expensive instruments, complex operating procedures and the requirement for professional technicians [6]. Therefore, the rapid and accurate determination of tetracycline in the environment and food is of great significance to health and safety.
[0003] Recently, fluorescent sensors, especially those based on carbon dots (CDs), have been used to detect tetracycline due to their fast response, easy operation, and high sensitivity [7]. Currently, most fluorescent sensors based on CDs are performed in solution and need to be tested in the laboratory, which poses challenges for transportation and real-time on-site detection. Therefore, there is an urgent need to develop a solid sensing platform that is easy to operate on-site and for rapid analytical sensing. Some solid sensing platforms reported in the literature are mainly paper-based sensors [8-11], but the inherent fluorescence of paper can interfere with the detection accuracy.
[0004] As a widely used soft material, hydrogels have attracted great attention from researchers. Incorporating carbon dots (CDs) into hydrogels helps to form gel materials with fluorescent properties. In addition, it has been shown that immobilizing CDs in hydrogels can effectively alleviate the aggregation quenching (ACQ) effect
[12] . Luo et al. reported the detection of tetracycline using a new non-toxic fluorescent molecular imprinted hydrogel based on cellulose nanocrystals and carbon dots
[13] . However, it is worth noting that the observed fluorescence changes still depend on laboratory instruments. In recent years, smartphones equipped with high-definition cameras have been continuously upgraded, making them ideal detection platforms [9,14-15]. Therefore, it is of great significance to develop a smartphone-assisted detection platform that uses carbon dot-based fluorescent hydrogels and smartphones to achieve on-site real-time detection of tetracycline. Summary of the invention
[0005] In order to solve the problem that the current tetracycline detection depends on laboratory instruments and cannot achieve on-site real-time detection, the present invention provides a dual-emission carbon dot and a visualized hydrogel sensing platform and application prepared therefrom.
[0006] The present invention is achieved by the following technical scheme: a dual-emission fluorescent carbon dot, wherein the dual-emission fluorescent carbon dot is: anise and m-phenylenediamine m-PD are dissolved in ultrapure water as precursors, and a one-pot hydrothermal method is used to control the reaction temperature to 220°C and react for 6 hours to synthesize the dual-emission fluorescent carbon dot DE-CDs.
[0007] The fennel is dried fennel seeds; the mass volume ratio of fennel, m-phenylenediamine and ultrapure water is 2:3:100 g / g / mL; and the fennel is dissolved in ultrapure water and then ultrasonically dispersed for 10 minutes.
[0008] The heating rate of the hydrothermal reaction is 4°C / min; the temperature is raised to 220°C, the reaction is carried out for 6 hours, and after natural cooling to room temperature, large particles are removed by filtration with filter paper, and a 0.22µm microporous membrane is used for secondary filtration to purify the product. The solution is freeze-dried to obtain a solid product, which is the dual-emission fluorescent carbon dot.
[0009] The present invention also provides an application of the dual-emission fluorescent carbon dots in detecting tetracycline TC, wherein the specific method is as follows: 0-230 μM TC is mixed into a 1 mg / mL DE-CDs aqueous solution, and the fluorescence emission spectrum is tested at excitation wavelengths of 345 nm and 406 nm, respectively, to establish a correlation between TC concentration and I 515 / I 432 Relationship between intensity ratios: I 515 / I 432 =0.2624exp(0.01429c)+0.2507, R 2 =0.9992; the detection limit LOD is 53.4nM, and the system response time is 4min.
[0010] The present invention also provides a visualized hydrogel sensing platform prepared by using the dual-emission fluorescent carbon dots, and the specific preparation method is as follows: (1) Preparation of agar-polyvinyl pyrrolidone (PVP) polymer hydrogel as a carrier material for DE-CDs: 1.0 g agar was dispersed in 100 mL ultrapure water by continuous heating until the agar was completely dissolved, and then 3.0 g PVP was added to obtain agar-PVP polymer hydrogel as a carrier material for DE-CDs; (2) Preparation of fluorescent hydrogel platform: 4.0 mL of DE-CDs solution with a concentration of 10.0 mg / mL was added to the agar-PVP polymer hydrogel obtained in step (1) and stirred for 30 min. Finally, the solution was spread evenly and dried at room temperature for 12 h to obtain the fluorescent hydrogel platform.
[0011] Furthermore, the thickness of the fluorescent hydrogel platform is 5-7 mm.
[0012] The present invention also provides application of the prepared visualized hydrogel sensing platform in on-site real-time detection of tetracycline TC.
[0013] The specific method is as follows: 650 μL of TC solution with different gradient concentrations is evenly added to the surface of the visual hydrogel sensing platform, and allowed to stand for 1 min. Then, a smartphone is used to record the color change of the fluorescent hydrogel under 365 nm ultraviolet light. The color index in the image is evaluated using a color recognition APP. The color is converted into brightness L, hue H, and saturation S values. The L / H ratio is calculated to evaluate the TC concentration. The ratio of L to H, L / H, varies with the TC concentration and shows a strong linear relationship in the range of 0-200 μM. A standard curve of sample concentration-color index is drawn. The linear relationship between L / H and TC concentration is: L / H=4.7901×10 -4 c(TC)+1.9490, R²=0.9970, and the detection limit LOD was 0.83μM.
[0014] The present invention uses Chinese herbal medicine fennel and m-phenylenediamine (m-PD) as precursors to synthesize dual-emission carbon dots (DE-CDs) through a one-pot hydrothermal method. No dialysis is required during the preparation process, and purified carbon dots can be obtained by direct filtration, thus saving time.
[0015] The prepared DE-CDs exhibit unique dual emission characteristics, with two independent emission wavelengths (432 nm and 515 nm) when the excitation wavelengths are 345 nm and 406 nm. Then a fluorescence sensor based on DE-CDs was established for sensitive and accurate detection of TC. In addition, a smartphone-assisted hydrogel sensing platform was implemented for visual and quantitative detection of TC. In conventional paper-based sensing platforms, the fluorescence of the filter paper itself will interfere with the identification and reading of colors during the detection process. The hydrogel prepared by the present invention has no fluorescence interference itself, which further improves the accuracy of the detection. Therefore, the dual-emission fluorescent carbon dot preparation visualization hydrogel sensing platform described in the present invention is expected to provide a new method for portable on-site rapid detection, thereby providing technical support for solving environmental pollution incidents. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Schematic diagram of the synthesis of DE-CDs and the detection of tetracycline based on fluorescence and hydrogel platform; Figure 2 Middle: (a) is the TEM image of DE-CDs; (b) is the size distribution of DE-CDs; (c) is the XPS spectrum of DE-CDs; (d) is C 1s XPS; (e) is N 1s XPS; (f) is O 1s XPS; Figure 3 AFM images of DE-CDs; Figure 4 is the FTIR graph of DE-CDs; Figure 5 Middle: (a) is the UV absorption spectrum, excitation spectrum 1 and emission spectrum 1 of DE-CDs; (b) is the 3D fluorescence emission spectrum of DE-CDs; (c) is the three-dimensional mapping of the excitation and emission wavelengths of DE-CDs; (d) is the excitation 2 and emission 2 spectra of DE-CDs; Figure 6 It is the fluorescence spectrum under the excitation wavelength of 300 nm-495 nm; Figure 7 Middle: (a) is the relationship between the fluorescence integral intensity of DE-CDs under 345nm excitation and ultraviolet absorbance; (b) is the relationship between the fluorescence integral intensity of quinine sulfate under 345nm excitation and ultraviolet absorbance; Figure 8 In the figure: (a) shows the effect of pH on the fluorescence intensity of DE-CDs (1.0 mg / mL); (b) shows the effect of NaCl concentration on the fluorescence intensity of DE-CDs (1.0 mg / mL); (c) shows the effect of temperature on the fluorescence intensity of DE-CDs (1.0 mg / mL); (d) shows the effect of H 2 O 2 , (e) the effect of UV irradiation on the fluorescence intensity of DE-CDs (1.0 mg / mL); (f) the effect of xenon lamp irradiation on the fluorescence intensity of DE-CDs (1.0 mg / mL); (g) the effect of room temperature storage time on the fluorescence intensity of DE-CDs (1.0 mg / mL); (h) the TGA of DE-CDs; Fig. 9 Middle: (a) shows the fluorescence quenching of DE-CDs at 432 nm in the presence of TC (0-230 μM), and the inset in the upper right corner is the relationship between the fluorescence intensity of DE-CDs at 432 nm and the TC concentration; (b) shows the fluorescence quenching of DE-CDs at 515 nm in the presence of TC (0-230 μM), and the inset in the upper right corner is the relationship between the fluorescence intensity of DE-CDs at 515 nm and the TC concentration; (c) shows the fluorescence quenching of DE-CDs at 515 nm in the presence of TC (0-230 μM), and the inset in the upper right corner is the relationship between the fluorescence intensity of DE-CDs at 515 nm and the TC concentration; 515 / I 432 It is exponentially related to TC concentration (0-118 μM); (d) is the selectivity of the system; (e) is the anti-interference ability of the system; Fig.10 The response time for DE-CDs to detect tetracycline; Fig.11In the figure: (a) is the UV-visible absorption spectrum of tetracycline, the excitation spectrum 1 and the emission spectrum 1 of DE-CDs; (b) is the UV-visible absorption spectrum of tetracycline, the excitation spectrum 2 and the emission spectrum 2 of DE-CDs; (c) is the fluorescence decay curve of DE-CDs without and with tetracycline; (d) is the UV-visible absorption spectrum of DE-CDs without and with tetracycline; Fig.12 Middle: (a) is the process of detecting TC using the fluorescent hydrogel platform; (b) is the color analysis photo of the fluorescent hydrogel and TC; (c) is the calibration curve of L / H and TC concentration. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0018] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, and the disclosure and materials cited therein are hereby incorporated by reference.
[0019] Technical equivalents to the specific embodiments described that are apparent to those skilled in the art using no more than routine experimentation are intended to be encompassed by this application.
[0020] The experimental methods in the following examples are all conventional methods unless otherwise specified. The instruments and equipment used in the following examples are all conventional laboratory instruments and equipment unless otherwise specified; the experimental materials used in the following examples are all purchased from conventional biochemical reagent stores unless otherwise specified.
[0021] 1. Experimental Methods 1. Synthesis of DE-CDs: DE-CDs were prepared by a hydrothermal method using anise and m-phenylenediamine as precursors. Specifically, 0.2 g of dried fennel seeds and 0.3 g of m-phenylenediamine were dissolved in 10 mL of ultrapure water and ultrasonically dispersed for 10 minutes. The resulting mixture was then transferred to a 50 mL Teflon autoclave and heated at 220 °C for 6 hours. After cooling to room temperature, larger particles were removed by filtration with filter paper, and then a 0.22 µm microporous membrane was used for secondary filtration to purify the product. Finally, the solution was lyophilized to obtain a solid product and stored at 4 °C for further experiments.
[0022] 2. Detection of TC by DE-CDs: TC with different concentrations (0-230µM) was mixed into an aqueous solution of DE-CDs (1mg / mL). Subsequently, the fluorescence emission spectra were tested at excitation wavelengths of 345nm and 406nm. The relationship between TC concentration and the I515 / I432 intensity ratio was established to evaluate the sensing ability of DE-CDs.
[0023] 3. Preparation of fluorescent hydrogel platform: (1) Preparation of agar-PVP polymer hydrogel as carrier material for DE-CDs: Agar (1.0 g) was dispersed in 100.0 mL ultrapure water under continuous heating until it was completely dissolved. Subsequently, PVP (3.0 g) was added to the solution.
[0024] (2) Then add 4.0 mL of DE-CDs solution (10.0 mg / mL) to the dissolved agar-PVP polymer hydrogel mixture and stir for 30 minutes. Finally, transfer the resulting solution (4.0 mL) to a clean 30 mm Petri dish and dry it at room temperature for 12 hours to obtain a fluorescent hydrogel platform with a thickness of 5-7 mm.
[0025] 4. Smartphone-assisted fluorescent hydrogel platform detection of TC: Different concentrations of TC (650 μL) were added to the surface of the prepared fluorescent hydrogel platform using a pipette to ensure uniform distribution over the entire surface. After one minute, the color change of the fluorescent hydrogel under 365 nm UV light was recorded using a smartphone camera. The color indicators in the image were evaluated using a color recognition APP, and the results were converted into sample concentrations using a standard curve to quantitatively evaluate TC.
[0026] 5. Analysis of TC in real samples: To evaluate the practicality of the fluorescence and smartphone-assisted thin-film sensors, we tested the content of TC in different water samples, including tap water, lake water, and river water. The tap water was obtained from the laboratory, while the lake water was obtained from Chenglong Lake (Lüliang College). The river water was obtained from Beichuan River (Lüliang City, Shanxi Province, China). Before analysis, all three types of real samples were filtered through a 0.22 μm microporous membrane to remove suspended particulate matter.
[0027] 2. Experimental Results 1. Characterization of DE-CDs: Figure 2 As shown, Figure 2 (a) is a TEM image of DE-CDs. The morphology and size of DE-CDs were evaluated using transmission electron microscopy (TEM). The image shows the remarkable dispersion of DE-CDs, which are nearly spherical with a lattice spacing of approximately 0.21 nm. The particle size of DE-CDs ranges from 1.28 to 5.76 nm, with an average particle size of 3.38 ± 0.06 nm ( Figure 2 b).
[0028] In addition, the AFM images ( Figure 3 ) shows that the average height of DE-CDs is 2.846 nm. The surface chemical structure of DE-CDs was analyzed by XPS. The complete XPS spectrum of DE-CDs ( Figure 2 c) Three apparent bands at 530.83 eV, 398.63 eV, and 284.08 eV are shown, corresponding to O1s, N1s, and C1s, respectively.
[0029] C1s spectra of DE-CDs ( Figure 2 d) is deconstructed into four peaks, namely C=C / CO (283.8 eV), CC (284.6 eV), C=N (285.3 eV) and C=O (287.4 eV). In the N 1s spectrum of DE-CDs ( Figure 2 e), three bands were observed at 398.6 eV, 399.5 eV, and 400.6 eV, indicating the presence of amino N, pyrrolic N, and graphitic N. O 1s spectrum ( Figure 2 f) There are two peaks at 530.7 eV and 531.9 eV, corresponding to C=O and CO, respectively.
[0030] The functional groups and surface chemical compositions of DE-CDs were further investigated using FTIR spectroscopy ( Figure 4 )。3340cm -1 The broad absorption bands at 1614, 1490, 1329, 1182 and 781 cm-1 are attributed to OH / NH stretching vibration. -1 The absorption peaks at are related to the stretching vibrations of C=O / C=N, C=C, CN, CO and CH, respectively[16-17]. The results of XPS and FTIR analysis confirmed the enhanced solubility of DE-CDs in water, which can be attributed to the presence of abundant carboxyl, hydroxyl and amino functional groups on their surfaces.
[0031] 2. Optical properties of DE-CDs: The UV-visible absorption spectrum of DE-CDs aqueous solution shows a clear peak at 209 nm ( Figure 5 a), indicating the π-π* transition of C=C and the n-π* transition of the sub-fluorescent group
[18] . In addition, a weak absorption peak was observed at 290 nm, which can be attributed to the n-π* transition of C=O / C=N
[19] . The optimal excitation wavelength (green line) and emission wavelength (red line) are located at 345 nm and 432 nm, respectively, with a Stokes shift of 87 nm. Figure 5b shows the three-dimensional fluorescence spectra of DE-CDs under different excitation wavelengths. It can be observed that when the excitation wavelength changes from 300 nm to 500 nm, the emission peak undergoes a significant red shift, showing two different centers. In addition, an additional peak becomes apparent as the excitation wavelength increases ( Figure 5 c). When the excitation wavelength is set to 406 nm, the corresponding emission wavelength is measured at 515 nm ( Figure 5 d). Excitation-independent and excitation-dependent fluorescence spectra show two distinct emission centers ( Figure 6 ). One of the centers is characterized by blue-dominated, excitation-independent emission. Notably, no significant shift in the emission center is observed when the excitation wavelength is in the range of 310 to 350 nm. This stability indicates an excitation-independent property, which can be attributed to the uniform and well-shaped surface of DE-CDs. In contrast, the emission center shifts when the excitation wavelength is changed from 400 to 490 nm. This phenomenon is attributed to the association of different energy levels with various functional groups that produce “surface states”
[20] . Using quinine sulfate as a reference, the quantum yield of DE-CDs is 30.48% ( Figure 7 ).
[0032] 3. In order to evaluate the feasibility of practical application, the stability of DE-CDs was studied ( Figure 8 ). Figure 8 ad showed that the fluorescence intensity of DE-CDs varied with pH value (2.0-13.0), NaCl concentration (0.5-3.0 M), temperature (20-96 °C) and H 2 O 2 The changes were minimal over the range of concentrations (0.1-1.0 M). Figure 8 e) and xenon lamp irradiation (18 min; Figure 8 f), the fluorescence intensity of DE-CDs did not change significantly. When DE-CDs were stored at room temperature for 90 days, a slight fluorescence decay was observed ( Figure 8 g). TGA analysis results ( Figure 8 h) shows that the weight loss is 1.43% at 137 °C, indicating that the prepared DE-CDs have excellent thermal stability.
[0033] 4. DE-CDs fluorescence detection of TC: As the TC concentration increases from 0 to 230 μM, the fluorescence intensity of DE-CDs aqueous solution at 432 nm ( Fig. 9 a) and 515 nm ( Fig. 9 b) are all lower. Figure 3 a and Figure 3The inset in the upper right corner of b shows the fluorescence intensity of DE-CDs versus TC concentration at emission wavelengths of 432 nm and 515 nm, respectively. Subsequently, we found that the fluorescence intensity ratio I515 / I432 showed a strong exponential relationship with TC concentration in the range of 0 to 118 μM, with an R² value of 0.9992 ( Fig. 9 c). According to the three-times standard deviation rule, the limit of detection (LOD) of TC was determined to be 53.4 nM. The reaction time of the system was 4 min ( Fig.10 ).
[0034] 5. For an excellent detection system, selectivity and anti-interference performance are crucial. Fig. 9 As shown in d, using Ag + 、Co 2+ 、Zn 2+ , Ca 2+ , Cu 2+ 、Cd 2+ , Pb 2+ , Ba 2+ Cr 2+ , K + ,La 2+ 、Ni 2+ 、Al 3+ Mg 2+ , Hg 2+ , Fe 3+ Sn 2+ , Mn 7+ 18 other metal ions (orange bars); Br - ,I - 、F - , Cl - , ClO 4 - , HS - , HSO 3 - , S 2 O 3 2- 、SCN - , H 2 PO 4 - The selectivity of the system was evaluated by 10 anions (yellow bars); 21 amino acids (green bars) including glycine, serine, valine, methionine, histidine, glutathione, tyrosine, arginine, cysteine, aspartic acid, threonine, glutamic acid, lysine, glutamic acid, alanine, leucine, isoleucine, phenylalanine, tyrosine, asparagine, and proline; and 11 antibiotics (dark green bars) including clindamycin, streptomycin, enrofloxacin, ciprofloxacin hydrochloride, ceftriaxone sodium, ampicillin, amoxicillin, ticarcillin, chlortetracycline, oxytetracycline, and tetracycline.
[0035] The fluorescence of DE-CDs can be quenched by tetracycline (TC), chlortetracycline (CTC) and oxytetracycline (OTC), while the effects of other substances are negligible. However, the quenching degree of OTC and CTC is not as obvious as that of TC. The above results show that the system can specifically identify tetracycline antibiotics, making it a highly selective sensor with practical application value. In the anti-interference experiment, DE-CDs showed excellent performance against the above substances ( Fig. 9 e).
[0036] Subsequently, the quenching mechanism of the DE-CDs fluorescence sensor for TC detection was analyzed. Fig.11 a shows that the UV-Vis absorption spectrum of TC overlaps with the fluorescence excitation spectrum 1 of DE-CDs. In addition, the excitation spectrum 2 of DE-CDs is consistent with the absorption spectrum of TC ( Fig.11 b). When the absorption spectrum of the quencher in the detection system overlaps with the excitation spectrum or emission spectrum of CDs, the internal filtering effect (IFE) occurs
[21] . Therefore, it can be concluded that the quenching mechanism may be attributed to the internal filtering effect. To further elucidate the quenching mechanism, the fluorescence lifetime and UV-Vis absorption peak of DE-CDs aqueous solution were examined after the addition of TC. Fig.11 As shown in c, after adding TC, the fluorescence lifetime remains almost unchanged. Similarly, after adding TC, the absorption peak of DE-CDs remains unchanged, indicating that no new substance is formed ( Fig.11 d). These evidences strongly support that the observed quenching mechanism is caused by the inner filter effect.
[0037] 5. Smartphone-assisted fluorescent hydrogel detection of TC: Fig.12 As shown in a, the prepared fluorescent hydrogel presents an almost colorless and transparent appearance. Adding different concentrations of TC will cause the color of the hydrogel to change, which can be directly perceived by the naked eye under 365 nm ultraviolet light ( Fig.12 b). After capturing a series of fluorescent images, a color recognition app was used to convert the corresponding colors into L (brightness), H (hue), and S (saturation) values, and the TC concentration was evaluated by calculating the L / H ratio. Fig.12 As shown in c, the ratio of L to H (L / H) varies with TC concentration and shows a strong linear relationship in the range of 0-200 μM (R²=0.9970), with a detection limit (LOD) of 0.83 μM. This finding indicates that the fluorescent hydrogel film is capable of quantitatively detecting TC.
[0038] Compared with previously reported TC detection methods (Table 1), the linear range of the constructed sensor is comparable to other methods. In addition, our proposed detection method using hydrogel film smartphone assistance stands out from existing methods, significantly improving the real-time nature of TC detection and providing greater portability for on-site real-time analysis of actual samples.
[0039] Table 1 Comparison of various tetracycline detection methods 6. Application in actual water samples: In order to demonstrate the validity and reliability of the developed method, tap water, Yuchenglong Lake water, and Dongchuan River water were collected and analyzed. Fluorescence detection and hydrogel membrane platform were used to detect TC in actual water samples. The recovery and relative standard deviation (RSD) of the method were calculated by adding different concentrations of TC to the water samples. As shown in Table 2, based on the fluorescence method, the recovery of TC in actual samples ranged from 98.13% to 102.80%, and the RSD was less than 4.17%. In contrast, the recovery and RSD of TC based on the hydrogel membrane platform were 95.73% to 105.57% and 4.05% to 7.82%, respectively. Although the results obtained from the hydrogel membrane platform were not as good as those obtained by fluorescence detection, they are of great value for on-site real-time testing.
[0040] Table 2 Tetracycline detection results in water samples The dual-emission carbon dots (DE-CDs) of the present invention were prepared by a simple one-step hydrothermal method. Subsequently, a fluorescent sensor with dual response signals was constructed for the detection of tetracycline. Moreover, when DE-CDs were combined with agar and PVP to form fluorescent hydrogel films, these composites facilitated the rapid detection of tetracycline by using a color recognition APP on a smartphone. In addition, the practicality of the constructed sensor was verified by evaluating the tetracycline content in water samples. More importantly, the organic combination of dual signal output and intelligent recognition improved the reliability of tetracycline detection results. The preparation and development of DE-CDs provides an effective strategy for combining laboratory precision testing with rapid on-site testing.
[0041] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
[0042] References: (1)Lin, M.; Zou, H. Y.; Yang, T.; Liu, Z. X.; Liu, H.; Huang, C. Z.An Inner Filter Effect Based Sensor of Tetracycline Hydrochloride asDeveloped by Loading Photoluminescent Carbon Nanodots in the ElectrospunNanofibers. Nanoscale 2016, 8 (5), 2999–3007. https: / / doi.org / 10.1039 / C5NR08177G. (2) Li, J.; Wang, X.; Shan, Y.; Huang, H.; Jian, D.; Xue, L.; Wang,S.; Liu, F. Handheld Inkjet Printing Paper Chip Based Smart TetracyclineDetector. Micromachines 2019, 10 (1), 27. https: / / doi.org / 10.3390 / mi10010027. (3) Li, P.; Rao, D.; Wang, Y.; Hu, X. Adsorption Characteristics ofPolythiophene for Tetracyclines and Determination of Tetracyclines in Fishand Chicken Manure by Solid Phase Extraction-HPLC Method. Microchemical Journal 2022, 173 , 106935. https: / / doi.org / 10.1016 / j.microc.2021.106935. (4) Yang, Y.; Lin, G.; Liu, L.; Lin, T. Rapid Determination of Multi-Antibiotic Residues in Honey Based on Modified QuEChERS Method Coupled withUPLC–MS / MS. Food Chemistry 2022, 374 , 131733. https: / / doi.org / 10.1016 / j.foodchem.2021.131733. (5) Wang, X.; Li, J.; Jian, D.; Zhang, Y.; Shan, Y.; Wang, S.; Liu,F. Paper-based antibiotic sensor (PAS) relying on colorimetric indirectcompetitive enzyme-linked immunosorbent assay for quantitative tetracyclineand chloramphenicol detection. Sensors and Actuators B: Chemical 2021, 329 ,129173. https: / / doi.org / 10.1016 / j.snb.2020.129173. (6) Mousavizadegan, M.; Hosseini, M.; Sheikholeslami, M. N.;Hamidipanah, Y.; Reza Ganjali, M. Smartphone Image Analysis-BasedFluorescence Detection of Tetracycline Using Machine Learning. Food Chemistry 2023, 403 , 134364. https: / / doi.org / 10.1016 / j.foodchem.2022.134364. (7) Huang, M.; Tong, C. A Dual-Emission Ratiometric FluorescenceProbe for Highly Selective and Simultaneous Detection of Tetracycline andFerric Ions in Environmental Water Samples Based on a Boron-Doped CarbonQuantum Dot / CdTe–Eu 3+ Composite. Environ. Sci.: Nano 2022, 9 (5), 1712–1723.https: / / doi.org / 10.1039 / D2EN00110A. (8) Ma, D.; Zhang, T.; Xing, H.; Wang, L.; Chen, D.; Wang, L. 3DPrinting-Based Lateral Flow Visual Assay Utilizing the Dual-ExcitationProperty of Nitrogen-Doped Carbon Dots for the Ratiometric Determination andChemometric Discrimination of Flavonoids. Microchim Acta 2024, 191 (6), 310.https: / / doi.org / 10.1007 / s00604-024-06383-4. (9) Wang, D.; Ding, X.; Xie, J.; Wang, J.; Li, G.; Zhou, X. A Three-in-One Versatile Sensor for Concise Detecting Biogenic Amines and BeefFreshness. Analytica Chimica Acta 2024, 1285 , 342025. https: / / doi.org / 10.1016 / j.aca.2023.342025. (10) Wang, L.; Lai, B.; Ran, X.; Tang, H.; Cao, D. A PortableSmartphone Platform Utilizing Dual-Sensing Signals for Visual Determinationof Semicarbazide in Food Samples. J. Mater. Chem. B 2024, 12 (14), 3469–3480.https: / / doi.org / 10.1039 / D4TB00001C. (11) Li, W.; Liu, F.; He, Y.; Song, G. A Ratiometric FluorescentSensor Based on S-Doped BCNO Quantum Dots and Au Nanoclusters Combined with3D-Printing Portable Device for the Detection of Malachite Green. Microchim Acta 2024, 191 (7), 394. https: / / doi.org / 10.1007 / s00604-024-06465-3. (12) Li, Y.; Young, D. J.; Loh, X. J. Fluorescent Gels: A Review ofSynthesis, Properties, Applications and Challenges. Mater. Chem. Front. 2019, 3 (8), 1489–1502. https: / / doi.org / 10.1039 / C9QM00127A. (13) Luo, Q.; He, S.; Huang, Y.; Lei, Z.; Qiao, J.; Li, Q.; Xu, D.;Guo, X.; Wu, Y. Non-Toxic Fluorescent Molecularly Imprinted Hydrogel Based onWood-Derived Cellulose Nanocrystals and Carbon Dots for Efficient Sorptionand Sensitive Detection of Tetracycline. Industrial Crops and Products 2022, 177 , 114528. https: / / doi.org / 10.1016 / j.indcrop.2022.114528. (14) Yan, L.; Zhang, B.; Zong, Z.; Zhou, W.; Shuang, S.; Shi, L.Artificial Intelligence-Integrated Smartphone-Based Handheld Detection ofFluoride Ion by Al3+-Triggered Aggregation-Induced Red-Emssion EnhancedCarbon Dots. Journal of Colloid and Interface Science 2023, 651 , 59–67. https: / / doi.org / 10.1016 / j.jcis.2023.07.125. (15) Ki, J.; Kwon, I. H.; Lee, J.; Lim, J.; Jang, S.; Son, S. U.;Seo, S. B.; Oh, S. Y.; Kang, T.; Jung, J.; Lee, K. G.; Hwang, J.; Lim, E.-K.A Portable Smartphone-Based Colorimetric Sensor That Utilizes DualAmplification for the on-Site Detection of Airborne Bacteria. Journal of Hazardous Materials 2023, 460, 132398. https: / / doi.org / 10.1016 / j.jhazmat.2023.132398. (16) Han, Y.; Kong, X.; Bao, R.; Yi, L.; Gu, Y.; Liu, L.; Lan, L.;Gan, Z.; Yi, J.; Zhang, X. Excitation-Dependent Photostability and HighFluorescence Quantum Yield of Cr-Doped Carbon Polymer Dots for Sensors,Anticounterfeiting Inks, and Light-Emitting Devices. ACS Appl. Nano Mater. 2024, 7 (2), 1674–1683. https: / / doi.org / 10.1021 / acsanm.3c04778. (17) Al-mashriqi, H. S.; Sanga, P.; Chen, J.; Qaed, E.; Xiao, J.; Li,X.; Qiu, H. Multifunctional Eu-Doped Carbon Dots Nanoprobe for HighlySensitive and Selective Determination of Glutathione in Biological Fluid andCell Imaging. Carbon 2024, 228 , 119380. https: / / doi.org / 10.1016 / j.carbon.2024.119380. (18) Yang, Z.; Xu, T.; Li, H.; She, M.; Chen, J.; Wang, Z.; Zhang,S.; Li, J. Zero-Dimensional Carbon Nanomaterials for Fluorescent Sensing andImaging. Chem. Rev. 2023, 123(18), 11047–11136. https: / / doi.org / 10.1021 / acs.chemrev.3c00186. (19) Mahto, M. Kr.; Samanta, D.; Shaw, M.; Shaik, M. A. S.; Basu, R.;Mondal, I.; Bhattacharya, A.; Pathak, A. Blue-Emissive Nitrogen-Doped CarbonDots for Picric Acid Detection: Molecular Fluorescence QuenchingMechanism. ACS Appl. Nano Mater. 2023, 6 (9), 8059–8070. https: / / doi.org / 10.1021 / acsanm.3c01523. (20) Tang, L.; Ji, R.; Cao, X.; Lin, J.; Jiang, H.; Li, X.; Teng, K.S.; Luk, C. M.; Zeng, S.; Hao, J.; Lau, S. P. Deep UltravioletPhotoluminescence of Water-Soluble Self-Passivated Graphene Quantum Dots. ACS Nano 2012, 6 (6), 5102–5110. https: / / doi.org / 10.1021 / nn300760g. (21) Zu, F.; Yan, F.; Bai, Z.; Xu, J.; Wang, Y.; Huang, Y.; Zhou, X.The Quenching of the Fluorescence of Carbon Dots: A Review on Mechanisms andApplications. Microchim Acta 2017, 184 (7), 1899–1914. https: / / doi.org / 10.1007 / s00604-017-2318-9. (22) Fan, Y.; Qiao, W.; Long, W.; Chen, H.; Fu, H.; Zhou, C.; She, Y.Detection of Tetracycline Antibiotics Using Fluorescent “Turn-off” SensorBased on S, N-Doped Carbon Quantum Dots. Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy 2022, 274 , 121033. https: / / doi.org / 10.1016 / j.saa.2022.121033. (23) Qi, H.; Teng, M.; Liu, M.; Liu, S.; Li, J.; Yu, H.; Teng, C.;Huang, Z.; Liu, H.; Shao, Q.; Umar, A.; Ding, T.; Gao, Q.; Guo, Z. Biomass-Derived Nitrogen-Doped Carbon Quantum Dots: Highly Selective FluorescentProbe for Detecting Fe3+ Ions and Tetracyclines. Journal of Colloid and Interface Science 2019, 539 , 332–341. https: / / doi.org / 10.1016 / j.jcis.2018.12.047. (24) Wang, X.; Zhu, C.; Yan, X.; Cheng, S.; Zhang, Y. The Synthesisof N‐doped Carbon Dots for Visual Differentiating and Detection ofTetracyclines. Luminescence 2023, 38 (2), 188–195. https: / / doi.org / 10.1002 / bio.4439. (25) Fan, Y.; Shen, L.; Liu, Y.; Hu, Y.; Long, W.; Fu, H.; She, Y. ASensitized Ratiometric Fluorescence Probe Based on N / S Doped Carbon Dots andMercaptoacetic Acid Capped CdTe Quantum Dots for the Highly SelectiveDetection of Multiple Tetracycline Antibiotics in Food. Food Chemistry 2023, 421 , 136105. https: / / doi.org / 10.1016 / j.foodchem.2023.136105. (26) Yuan, M.; An, J.; Zhang, G.; Hu, Y.; Luo, M.; Shi, Y.; Liu, Y.In-Situ Nitrogen-Doped Carbon Dots for Fluorescence Sensing of TetracyclineAntibiotic. Ceramics International 2022, 48 (3), 4047–4054. https: / / doi.org / 10.1016 / j.ceramint.2021.10.194. (27) Liu, Y.; Liu, B.; Huang, P.; Wu, F.-Y.; Ma, L. Concentration-Dependent Photoluminescence Carbon Dots for Visual Recognition and Detectionof Three Tetracyclines. Anal Bioanal Chem 2021, 413 (9), 2565–2575. https: / / doi.org / 10.1007 / s00216-021-03221-x. (28) Xiong, J.; Yang, L.; Gao, L. X.; Zhu, P. P.; Chen, Q.; Tan, K.J. A Highly Fluorescent Lanthanide Metal-Organic Framework as Dual-ModeVisual Sensor for Berberine Hydrochloride and Tetracycline. Anal Bioanal Chem 2019, 411 (23), 5963–5973. https: / / doi.org / 10.1007 / s00216-019-02004-9. (29) Miao, J.; Ji, W.; Yu, J.; Cheng, J.; Huang, Y.; Arabi, M.; Zhou,N.; Li, B.; Zhang, Z.; Chen, L.; Wang, X. A Triple-Emission RatiometricFluorescence Sensor Based on Carbon Dots-Au Nanoclusters Nanocomposite forDetection of Tetracycline. Sensors and Actuators B: Chemical 2023, 384 , 133636.https: / / doi.org / 10.1016 / j.snb.2023.133636. (30) Zhang, L.; Zhang, X.; Xu, Y.; Xu, J.; Huang, Y.; Yuan, Y.; Jia,L. Portable Luminescent Fiber- and Glove-Based Nanosensor for MulticolorVisual Detection of Tetracycline in Food Samples. Microchim Acta 2024, 191 (4),225. https: / / doi.org / 10.1007 / s00604-024-06306-3。
Claims
1. A dual-emission fluorescent carbon dot, characterized in that: The dual-emission fluorescent carbon dots are: anise and m-phenylenediamine m-PD are dissolved in ultrapure water as precursors, and the dual-emission fluorescent carbon dots DE-CDs are synthesized by a one-pot hydrothermal method with the reaction temperature controlled at 220° C. and the reaction time at 6 h.
2. The dual-emission fluorescent carbon dots according to claim 1, characterized in that: The fennel is dried fennel seeds; the mass volume ratio of fennel, m-phenylenediamine and ultrapure water is 2:3:100 g / g / mL; and the fennel is dissolved in ultrapure water and then ultrasonically dispersed for 10 minutes.
3. The dual-emission fluorescent carbon dots according to claim 1, characterized in that: The heating rate of the hydrothermal reaction is 4°C / min; the temperature is raised to 220°C, the reaction is carried out for 6 hours, and after natural cooling to room temperature, large particles are removed by filtration with filter paper, and a 0.22µm microporous membrane is used for secondary filtration to purify the product. The solution is freeze-dried to obtain a solid product, which is the dual-emission fluorescent carbon dot.
4. Use of the dual-emission fluorescent carbon dots according to any one of claims 1 to 3 in detecting tetracycline TC, characterized in that: The specific method is: 0-230μM TC was mixed into 1mg / mL DE-CDs aqueous solution, and the fluorescence emission spectrum was tested at 345nm and 406nm excitation wavelengths to establish the relationship between TC concentration and I 515 / I 432 Relationship between intensity ratios: I 515 / I 432 =0.2624exp(0.01429c)+0.2507, R 2 =0.9992; the detection limit LOD is 53.4nM, and the system response time is 4min.
5. A visualized hydrogel sensing platform is prepared using the dual-emission fluorescent carbon dots according to any one of claims 1 to 3, characterized in that: The specific preparation method is: (1) Preparation of agar-PVP polymer hydrogel as a carrier material for DE-CDs: 1.0 g agar was dispersed in 100 mL ultrapure water under continuous heating until the agar was completely dissolved, and then 3.0 g PVP was added to obtain agar-PVP polymer hydrogel as a carrier material for DE-CDs; (2) Preparation of a fluorescent hydrogel platform with dual response signals: 4.0 mL of a 10.0 mg / mL DE-CDs solution was added to the obtained agar-PVP polymer hydrogel in step (1) and stirred for 30 min. Finally, the solution was spread evenly and dried at room temperature for 12 h to obtain a visualized hydrogel sensing platform.
6. The method of preparing a visualized hydrogel sensing platform using dual-emission fluorescent carbon dots according to claim 5, characterized in that: The thickness of the fluorescent hydrogel platform is 5-7 mm.
7. Use of the visualized hydrogel sensing platform prepared according to claim 5 in on-site real-time detection of tetracycline TC.
8. The use according to claim 7, characterized in that: The specific method is as follows: 650 μL of TC solution with different gradient concentrations is evenly added to the surface of the visual hydrogel sensing platform, and allowed to stand for 1 min. Then, a smartphone is used to record the color change of the fluorescent hydrogel under 365 nm ultraviolet light. The color recognition software is used to evaluate the color index in the image. The color is converted into brightness L, hue H and saturation S values. The L / H ratio is calculated to evaluate the TC concentration. The ratio of L to H, L / H, varies with the TC concentration and shows a strong linear relationship in the range of 0-200 μM. A standard curve of sample concentration-color index is drawn. The linear relationship between L / H and TC concentration is: L / H=4.7901×10 -4 c(TC)+1.9490, R²=0.9970, and the detection limit LOD was 0.83μM.
Citation Information
Cited By
Double-emission carbon dot hydrogel film as well as preparation method and application thereof
CN121975258A
Fluorescent carbon dots, hydrogel and application thereof, and enrofloxacin detection method
CN122302873A